Emerging advancements in 3D food printing - Prithviraj, V.; Díaz, Luis Puente; Lemus-Mondaca, Roberto; Ullah, Aman; Roopesh, M. S. (Frontiers in Food Science and Technology, 2025)
In recent years, three-dimensional (3D) food printing has seen substantial advancements, facilitating the production of highly customizable food products by integrating complex design and functional elements. This technology allows for fine-tuning visual characteristics, nutritional content, texture, and organoleptic properties according to individual consumer needs. Recently, 3D food printing has been used to encapsulate bioactive compounds to increase the nutritional value of food products. In addition, 3D printing has been explored for developing meat and cheese alternatives, cell-cultured meat, and scaffold development in cellular agriculture to obtain more efficient and personalized processes for food production. This review systematically examines recent progress in 3D food printing, focusing mainly on the applications in the domains mentioned above, and discusses the challenges and future research directions. Thus, this review can guide future research to achieve better 3D printed products using these emerging methods.